Leisure activity associated with cognitive ability level, but not cognitive change - Gow, Alan J.; Avlund, Kirsten; Mortensen, Erik L. (Frontiers in Psychology, 2014)
Although activity participation is promoted as cognitively-protective, critical questions of causality remain. In a cohort followed every five years from age 75 to 85 years, potential reciprocal associations between level and change in leisure activity participation and level and change in cognitive abilities were examined. Participants in the Glostrup 1914 Cohort, a longitudinal study of ageing, completed standardised cognitive ability tests and reported their leisure activity participation (11 activities defined a leisure activity score) at ages 75, 80 and 85. Higher leisure activity was associated with higher cognitive ability (significant correlations ranged from .15 to .31, p < .05). Between ages 75 and 85, participation in leisure activities and cognitive ability declined significantly. Growth curve models, which provided latent variables for level of and 10-year change in both leisure activity and cognitive ability, confirmed the positive association between levels of leisure activity and cognitive ability (path coefficient = .36, p < .001); however, leisure activity level or change was not associated with cognitive change. Although a positive association between leisure activity and cognitive ability was reported—the likely precedents of this are discussed—there was no evidence that a higher level or maintenance of leisure activity was protective against cognitive decline across a 10-year follow-up.